Pilot Unit for Investigation of Small-Size Diesel Engines Operation - D. A. Shkurko (Наука и техника)
The paper describes a pilot unit for investigation of small-size diesel engines operation. This engine operational process has been investigated with the help of a piezoelectric indicator. The developed pilot unit allows to reveal the ways for improvement of technical and economical indices of the parameters of the diesel engines to be investigated.